The 41st International ACM SIGIR Conference on Research &Amp; Development in Information Retrieval 2018
DOI: 10.1145/3209978.3210118
|View full text |Cite
|
Sign up to set email alerts
|

WikiPassageQA

Abstract: With the rise in mobile and voice search, answer passage retrieval acts as a critical component of an effective information retrieval system for open domain question answering. Currently, there are no comparable collections that address non-factoid question answering within larger documents while simultaneously providing enough examples sufficient to train a deep neural network. In this paper, we introduce a new Wikipedia based collection specific for nonfactoid answer passage retrieval containing thousands of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…This is in line with recent work in ad-hoc retrieval, which showed that BERT models trained on tweets and Wikipedia data transfer surprisingly well to news articles (Akkalyoncu Yilmaz et al, 2019). Other work has shown that IR baselines are often hard to beat, e.g., most neural models trained in-domain on WikiPassageQA perform below BM25 (Cohen et al, 2018). In contrast, we show that a large number of BERT models from a variety of 140 domains outperform these baselines without requiring any in-domain supervision.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This is in line with recent work in ad-hoc retrieval, which showed that BERT models trained on tweets and Wikipedia data transfer surprisingly well to news articles (Akkalyoncu Yilmaz et al, 2019). Other work has shown that IR baselines are often hard to beat, e.g., most neural models trained in-domain on WikiPassageQA perform below BM25 (Cohen et al, 2018). In contrast, we show that a large number of BERT models from a variety of 140 domains outperform these baselines without requiring any in-domain supervision.…”
Section: Resultssupporting
confidence: 87%
“…Typically, one answer is correct. • WikiPassageQA (Cohen et al, 2018) was crowd-sourced from Wikipedia articles and is not restricted to a particular domain (although many questions are about history topics). Candidate answers are passages from a single doc-ument, on the basis of which the question was formulated.…”
Section: Answer Selection (As)mentioning
confidence: 99%
See 1 more Smart Citation
“…Two datasets were used to evaluate this model. First with WikiPassageQA (Cohen et al, 2018) consists of 4165 question-answer pairs. This dataset was created from the Wikipedia text and the questions were created by crowd sourcing.…”
Section: Findings Datasetmentioning
confidence: 99%
“…Question answering Although they may not be not strictly formulated as questions, retrieval for complex topics is related to approaches that answer questions from web content. Retrieval techniques for effective question answering is undergoing a resurgence of research, with a particular interest in non-factoid QA [2], [3]. These works are similar to complex answer retrieval in that they perform question answering by retrieving relevant passages, in particular paragraphs from Wikipedia.…”
Section: Background and Related Workmentioning
confidence: 99%